XPS study of the surface chemistry on AZ31 and AZ91 magnesium alloys in dilute NaCl solution - Wang, Lei; Shinohara, Tadashi; Zhang, Bo-Ping (Applied surface science, 2010)
The surface chemistry on AZ31 and AZ91 magnesium alloys was characterized by X-ray photoelectron spectroscopy (XPS) in the corrosion and the passivation zones. In the corrosion zone, the presence of Mg(OH) 2 and MgCO 3 species was found in the outer surface, whereas, in the inner layer, the co-existence of Mg(OH) 2, MgO and MgCO 3 species was observed for both alloys. The presence of Al 3+ in the surface electrolyte to form Al 2O 3/Al(OH) 3 and the formation of carbonate product provide a better passivation on the surfaces and retard the chloride-induced corrosion on the materials in the passivation zone.